Novels and other writings - West, Nathanael (The Library of America, 1997)
Novels and Other Writings is the most complete West now available in a single volume. Film buffs will be particularly fascinated by Miss Lonelyhearts, which served as the basis for two intriguing movies and The Day of the Locust, West's final novel, which many consider to be the most withering attack on Hollywood ever written. Among the papers included in this collection are a never-filmed screenplay, Before the Fact, and a screen treatment of West's novel A Cool Million